Latent gaps in business education attaining globalisation in Taiwan. Issue 3 (8th August 2016) - Hsu, Jane Lu; Feng, Chih-Hung; Hsu, Cherie
Abstract : Purpose: This study aims to investigate how globalised business programmes in higher education in Taiwan fills latent gaps between business education and the local job markets from viewpoints of teachers, students in higher education, and those working in the job markets within five years of graduation. The distinction in viewpoints from teachers, students, and graduates is valuable in examining how globalised business programmes in Taiwan help students in competitiveness in the local job markets. Design/methodology/approach: Six teachers (five males, one female) in business programmes from two national universities with teaching experiences ranging from two years to 19 years were interviewed. Ten students (four males, six females) in business programmes from six universities ranging from junior to master's level were interviewed. Nine people (five males, four females) who were working full-time in the local job markets within five years of graduation from business programmes were interviewed. A total of 25 subjects (14 males, 11 females) participated in the study. Findings: In course-related issues, students seem to have difficulties in understanding certain issues with different cultural background, and this affects teachers using textbooks and cases with US or European standpoints. In applicability, some teachers believe it is students' responsibilities to know how to apply what they have learned in school in practice. Those graduates who are working in local markets explained that in reality they do not apply much of what they have learned in globalised business programmes at work. In crossing over the gap, some teachers try to include local cases in teaching materials. Research limitations/implications: The argument in this study is not to lose the beauty of localisation in globalisation in business programmes in higher education. The latent gaps between globalised business programmes and local job markets can be crossed over with a strong foundation of training in theories in globalised business programmes plus some experiences obtained in working experiences. Originality/value: Findings in this study provided new insights into gaps between globalised business programmes and local job markets, and how it can be crossed over with a strong foundation of training in theories plus experiences obtained in practical training. Generic competence and transferable skills in local business operations ought to be included in globalised business programmes.